The impact of service quality, price, and perceived convenience on customer loyalty in conventional building material stores - Utari, Ida Ayu Made Dwi; Raditya, I Wayan Angga (Review of Management, Accounting, and Business Studies, 2023)
The study aimed to determine the effect of service quality, price, and perceived convenience on customer loyalty at the building material store UD. Puspa Nadi, located in Badung Regency. The population in this study comprised all residents of Badung Regency, totaling 543,681 people. The sampling technique used was purposive sampling, which involves selecting respondents based on specific criteria to ensure they are relevant to the study topic. The number of respondents was determined using the Slovin formula, resulting in a total sample of 100 respondents. The data analysis technique used to test the hypotheses in this study was multiple linear regression analysis. Based on the results, it was found that service quality, price, and perceived convenience had a significant positive effect on customer loyalty, both partially and simultaneously. These results indicate the higher the quality of services provided by UD. Puspa Nadi, the more affordable the prices of building materials offered to consumers, and the higher the perception of customer convenience when transacting with UD. Puspa Nadi, the greater the increase in customer loyalty.